(untitled) (American Journal of Interdisciplinary Research and Innovation, 2025)
This study investigates the influence of emotional intelligence (EI) and community support on school crisis management in Tagbina District 1, Surigao del Sur, Philippines. A descriptive-correlational research design was used, surveying 214 respondents, including school heads, teachers, and stakeholders. Findings revealed that student bullying and violence was identified as the most frequent crisis experienced in the past five years, with a mean rating of 3.550 (often category). In terms of community support, partnerships with local communities and organizations had the highest mean rating of 4.540 (always category), reflecting strong external collaboration. Among crisis leadership dimensions, instructional leadership had the highest mean of 4.428 (always category), emphasizing the role of guiding teachers and students during crises. Results further indicate a significant positive correlation between EI and crisis leadership effectiveness (r = 0.421, p < 0.01), with empathy showing the strongest relationship in instructional (r = 0.780, p < 0.01), organizational (r = 0.553, p < 0.01), and community extension leadership (r = 0.406, p < 0.01), while self-management was most strongly associated with human resource (r = 0.386, p < 0.01) and strategic leadership (r = 0.467, p < 0.01). Findings suggest the need for EI training programs for school leaders and strengthened community collaboration to improve crisis resilience.